MEMBANGUN PERDAMAIAN LINTAS IMAN MELALUI PENDEKATAN INTERRELIGIUS DALAM PENDIDIKAN ISLAM: BELAJAR DARI PESANTREN SOKO TUNGGAL - Achmad Muhibin Zuhri (Universitas Islam Lamongan, 2021)
Conflicts and sentiments between religions in Indonesia have yet to be fully resolved convincingly. This is because many parties still use their beliefs to mobilize interests. Recognizing this phenomenon, this article seeks to examine and analyze the experiences carried out by the Soko Tunggal Islamic Boarding School in mitigating conflict through an inter-religious approach in the praxis of Islamic Religious education. Through qualitative research methods, data were obtained through interviews, observation, and documentation of important data in the field, which in the following stages were analyzed using a multidisciplinary perspective. This study found that the inter-religious approach in the context of Islamic education was carried out to minimize the potential for inter-religious conflict. Through the involvement of religious figures, interfaith dialogue does not want to make Islam a syncretic religion. Through this approach, Islamic education is articulated not only in exclusive-primordial academic activities. But it also opens up space for intellectual awareness that Muslims are an integral part as citizens of the world who are entrusted with maintaining social harmony based on divine, human, and national values.